2014
DOI: 10.3402/gha.v7.25754
|View full text |Cite
|
Sign up to set email alerts
|

Does moonlighting influence South African nurses’ intention to leave their primary jobs?

Abstract: BackgroundStaff retention and turnover have risen in prominence in the global discourse on the health workforce. Moonlighting, having a second job in addition to a primary job, has not featured in debates on turnover.ObjectiveThis paper examines whether moonlighting is a determinant of South African nurses’ intention to leave their primary jobs.DesignDuring 2010, a one-stage cluster random sample of 80 hospitals was selected in four South African provinces. On the survey day, all nurses working in critical car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 52 publications
(90 reference statements)
1
15
0
Order By: Relevance
“…And higher than 33% of nurses in twelve European countries [35]. It is also higher than the 30.9% in South Africa [36], 24.3% [10] in Saudi Arabia and higher than three study results…”
Section: Discussionmentioning
confidence: 55%
“…And higher than 33% of nurses in twelve European countries [35]. It is also higher than the 30.9% in South Africa [36], 24.3% [10] in Saudi Arabia and higher than three study results…”
Section: Discussionmentioning
confidence: 55%
“…The participants were predominantly middle-aged, with a mean age of 41.5 (SD: 10.4) years. The unweighted demographic and background characteristics of the 3,784 nurses recruited in the four study provinces are shown elsewhere in this special journal issue ( 45 ). Importantly, 40.7% (95% CI: 35.3–46.4) of nurses indicated that they had moonlighted or worked for an agency in the 12 months prior to the survey.…”
Section: Resultsmentioning
confidence: 99%
“…In nursing, fiscal austerity has led to stagnating wages and the freezing of posts, producing problems of poor retention and a shift towards casualization. Unable to fill posts or to afford permanent positions, many hospitals meet short-term demands by recruiting via agencies or paying existing staff to work overtime, with potentially detrimental effects on healthcare delivery (Rispel and Blaauw 2015;Rispel et al 2014a). A large cross-sectional survey reveals the scale of casualization in nursing, showing that as many as 70 per cent of nurses combine their formal jobs with moonlighting, overtime and agency work.…”
Section: Middle-class Aspiration In a Time Of Austeritymentioning
confidence: 99%